A Study of Color Distortion on Specimen Photography Using the Same Object on Different Background Colors - Buawatana, Chaiyut; Pittayawaranant, Bansha; Sookpatti, Wicha; Ratanarapee, Samrerng (Siriraj Medical Journal, 2003)
Due to an attempt to take photographs of colorful flowers on 5 different background colors, it was found that the color of the background in every photograph looked natural but the color of the flowers seemed to be distorted in both color tone and brightness. The only photograph that provided the most natural image was the one using black as the background color. It was obvious that the darker the flower’s color was, the more color distortion would be found. This finding Ied to a question that "When it comes to specimen photography, will there be any color distortion as found in this one?". A study was then conducted using fresh liver tissue and formalin-fixed liver tissue with 5 difference background colors ; black, deep blue, green; light grey and red. The study indicated that black background provided the most natural image while deep blue caused a very slight distortion and the other three caused even more distortion. The study also revealed that the fresh specimens may cause more distortion than the formalin-fixed ones.